2007
DOI: 10.1093/ndt/gfm051
|View full text |Cite
|
Sign up to set email alerts
|

Kidney dysfunction as a risk factor for first symptomatic stroke events in a general Japanese population--the Ohasama study

Abstract: Decreased kidney function increased the risk of first symptomatic stroke events in a general Japanese population. The high prevalence of stroke in this population prompts the need for greater public awareness about risks for CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
106
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(122 citation statements)
references
References 18 publications
7
106
2
3
Order By: Relevance
“…Renal dysfunction is an independent risk factor for death and/or cardiovascular disease (CVD) events among the general population [1,2]. Although the reason why renal dysfunction increases CVD mortality and morbidity is unclear, the accumulated evidence suggests the major participation of oxidative stress (OS) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Renal dysfunction is an independent risk factor for death and/or cardiovascular disease (CVD) events among the general population [1,2]. Although the reason why renal dysfunction increases CVD mortality and morbidity is unclear, the accumulated evidence suggests the major participation of oxidative stress (OS) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulative evidence has revealed that a decreased glomerular filtration rate (GFR) and the presence of proteinuria are independent risk factors for death and/or cardiovascular disease (CVD) events among general populations (1)(2)(3). Thus, it is now recognized that chronic kidney disease (CKD) (4) is an emerging new target for investigation from the viewpoint of public health.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 A number of prospective studies have also disclosed CKD as a risk factor for another vascular disease: Stroke. [5][6][7] In the Rotterdam study, having CKD was a risk factor for only hemorrhagic but not for ischemic stroke. 8 A recent study showed sex difference as a risk factor in CKD that was associated with hemorrhagic stroke in men but ischemic stroke in women.…”
Section: Introductionmentioning
confidence: 99%